Perception of local people and visitors towards ecotourism development in Jagadishpur reservoir - Aryal, Bishal; Chhetri, Vivek Thapa; Khanal, Pramisha (International Journal of Environment, 2022)
Ecotourism promotes stewardship of natural and cultural resources. However, local people and tourists' opinions are necessary to promote ecotourism development. This study attempts to identify prospective ecotourism products and assess local and visitor perceptions towards ecotourism development in the Jagadishpur reservoir. We conducted semi-structured interviews with 50 local households, 65 visitors, and 7 key informants. We used Friedman's rank test to determine the preferences for ecotourism products, and Fisher's exact test to quantify locals and visitors' perceptions of ecotourism. The findings showed that lakes/scenic beauty, and bird watching are the highest rated ecotourism products by locals and visitors, respectively. Local people and visitors perceived picnic spots and view towers as additional ecotourism products for ecotourism development, respectively. The perceptions of locals and visitors showed no significant difference that the area is suitable for ecotourism, biodiversity conservation, and livelihood promotion of locals. However, a significant difference was found in the perception between locals and visitors of the culture and tradition. The study showed that local people and visitors both are positive for ecotourism development in terms of suitability, livelihood, and biodiversity conservation. Detailed understanding and prioritized ecotourism products can contribute to ecotourism promotion more effectively. Furthermore, more research on the feasibility of identified ecotourism products and the effectiveness of fund allocation for ecotourism products are urgently needed to develop wetland tourism in a sustainable way.